Development Of Flipbook Media Based On "Indonesian Culture" as an Effort to Strengthen The Character Education Of Elementary School Students - Septyana Dwi Kusumawardani; Candra Dewi; Naniek Kusumawati (ISTAWA, 2023)
This research is a development research. The subject of this research is the development of flipbook-based learning media. This research uses a method by applying Research and Development (RD). The media developed in this study used the ADDIE model which consists of 5 stages, namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation.This study aims to develop Indonesian culture-based flipbook learning media as a strengthening of character education in elementary school students.  The data collection techniques that researchers use are observation, interviews, questionnaires, evaluation and documentation. The results of the study can be concluded that the flipbook learning media is very feasible to use. This is obtained based on the percentage of validation results and product trials. The percentage results obtained include media experts showing a percentage of 92.2% with very feasible criteria, material experts showing a percentage of 100% with very feasible criteria, language experts showing a percentage of 93.8% with very feasible criteria. Based on the student response questionnaire assessment, it shows a percentage of 87.3% with very feasible criteria, the teacher response questionnaire assessment shows a percentage of 98% with very feasible criteria, the results of the learning evaluation that students have done show a percentage of 90% with very feasible criteria.